COIDIC: a new strategy? - (:unkn) unknown (My University, 2019)
We analyze and translate in this working paper a press release published on December 13, 2019 on the MOFCOM website, which sets out what could constitute an evolution in the approach to the African market by Chinese service providers. The pretext for this communiqué is the agreement concluded in Guinea between the Administration for the Control of Major Projects and Public Procurement and a Chinese investment fund, COIDIC - that is, the China Overseas Infrastructure Development Investment Co., Ltd.
Keywords: African Research